Impact of European Data Protection Reform on direct marketing - Kornejeva, Alise (Riga Graduate School of Law, 2019)
This study explored the influence of the legislation adopted under the EU Data Protection Reform on the direct marketing. Since the introduction of the previous data protection legislation, the amount of data collected, processed and stored has grown exponentially, resulting in the increased risk to the data security of an individual. Thereby, introduction of new rules is a necessity in order to achieve proper execution of data subject’s rights in the digital age and create efficient and simplified rules for the companies to apply. Direct marketing is based on the actions connected to personal information – data is gathered via cookies, stored for the purposes of communication and analyzed in order to provide targeted advertising. Thus, it is necessary for companies and especially direct marketers to understand the provisions of the enforced and upcoming legislation and adjust their marketing strategies and overall company structure to them in order to achieve compliance.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Data protection; Direct marketing